The state of American democracy after Trump. Issue 1 (April 2022) - Arvanitopoulos, Constantine
Democracy is retreating worldwide. As Freedom House reports, the US has not escaped this trend. The system of checks and balances of American democracy managed to thwart Trump's assault on democracy. But together with longstanding institutional and structural defects, his presidency clearly indicates that American democracy is on the verge of political decay. Political polarisation, inequalities, identity politics and the inability of the two political parties to reach compromises are further testing the American democratic institutions. To avert decay, the US needs a reform coalition to bring about institutional changes; and more importantly, to establish inclusive economic policies and a renewed focus on citizenship, duty and a shared purpose.